A science that knows no country: Pandemic preparedness, global risk, sovereign science. Issue 2 (December 2017) - Hurlbut, J Benjamin
This paper examines political norms and relationships associated with governance of pandemic risk. Through a pair of linked controversies over scientific access to H5N1 flu virus and genomic data, it examining the duties, obligations, and allocations of authority articulated around the imperative for globally free-flowing information and around the corollary imperative for a science that is set free to produce such information. It argues that scientific regimes are laying claim to a kind of sovereignty, particularly in moments where scientific experts call into question the legitimacy of claims grounded in national sovereignty, by positioning the norms of scientific practice, including a commitment to unfettered access to scientific information and to the authority of science to declare what needs to be known, as essential to global governance. Scientific authority occupies a constitutional position insofar as it figures centrally in the repertoire of imaginaries that shape how a global community is imagined: what binds that community together and what shared political commitments, norms, and subjection to delegated authority are seen as necessary for it to be rightly governed.